دور خزعة وبزل النقي في تشخيص الأمراض الدموية وغير الدموية (السليمة والخبيثة) - حسين فراس; أحمد عيسى; حاج محمد نور (Latakia University Journal -Medical Sciences Series, 2018)
Background: Bone marrow screening is an important diagnostic tool that is indispensable especially in the diagnosis of hematological diseases and fairly non- hematological diseases that cause disturbances in the work of bone marrow. There are two ways to examine the bone marrow through an aspiration or biopsy. They are complementary, as they achieve a thorough evaluation of bone marrow rite and provide the ultimate interpretation most often. It is a simple, easy to operate and relatively safe method. In addition, bone marrow studying is an important procedure for determining the degree and stage of the disease, the identification of alarm agents, and the evaluation of the therapeutic response in some disorders. And it is essential to keep in mind the recent complementary tests of immunfinotyping, molecular genetics ,cytogenetic and its role in determining therapeutic and prognostic bases. Methods: The study was conducted on the patients who visited the Division of Hematology at Alasad and Tishreen University Hospitals between May 2015 and 2016 who gave a Contraindicated to study bone marrow such as pancytopenia,anemia, high ESR, thrombocytopenia. A detailed clinical story was taken. Clinical examination assessment were recorded from paleness, fatigue, lack of appetite or weight loss, enlargement of lymph nodes, or Splenomegaly and Hepatic hyperplasia, was also investigated .Laboratory valves were recorded for patients. We performed bone marrow removal and biopsy for all patients enrolled in the study, and Bone marrow aspiration was read by a Hematologist, and Bone marrow biopsy was also read by a pathologist. Results: The biopsy was diagnosed in 120 cases compared to 64 cases diagnosed by aspiration, the sensitivity and quality of the biopsy was 100% for the diagnosis of metastases mylofibrosis and aplastic anemia . The quality of the aspiration was high for the diagnosis of mylodysplasia syndrome and infections. While the sensitivity of the aspiration was high for the diagnosis of metastases bone marrow and mylofibrosis. The most frequently observed diagnosis in study patients was tumor metastases. Conclusion: Bone marrow aspiration and biopsy are two important, complementary procedures for diagnosis and bone marrow studying. It is preferable to conduct a bone marrow study in the elderly when there is abnormal hematological. When there is an isolated anemia or pancytopenia, it is preferable to perform both bone marrow aspiration and biopsy because this increases the rate of access to the diagnosis. To evaluate complete remession of tumers in patients undergoing chemotherapy, bone marrow biopsy is preferred. In case of suspicion of the presence of an infectious disease caused by the laboratory hematological disorder, it is preferable to only perform aspiration. Bone marrow biopsy should be performed at each hypo cellular aspiration. المقدمة: فحص نقي العظم هو أداة تشخيصية هامة لا غنى عنها في تشخيص الأمراض الدموية خاصة والامراض غير الدموية الى حد ما التي تسبب اضطرابات في عمل النقي. هناك وسيلتان لفحص النقي اما عبرالبزل أو الخزعة وهما عينتان متكاملتان كونهما تحققان تقييم شامل للنقي وتقدمان التفسير النهائي في معظم الأحيان. وهي وسيلة بسيطة و سهلة الاجراء وامنة نسبيا . وبالإضافة إلى ذلك، تعد إجراء هام لتحديد درجة ومرحلة المرض و تعيين عوامل الانذار وكذلك في تقييم الاستجابة العلاجية في بعض الاضطرابات. ولا ننسى الاختبارات التكميلية الحديثة من التألق المناعي و الدراسة الخلوية الوراثية والجزيئية ومالها من دور في تحديد أسس علاجية وانذارية الطرائق: شملت عينة البحث المرضى المراجعين لشعبة أمراض الدم في مشفيي الاسد و تشرين الجامعيين في اللاذقية ولديهم استطباب لدراسة نقي العظم تشمل فقر دم غير مفسر ،نقص عناصر دم،نقص او ارتفاع صفيحات ،ارتفاع سرعة تثفل ،ضخامات عقدية اوحشوية،حمى مجهولة السبب علما انه تم استبعاد عينات المرضى التي تم تشخيصها بسهولة بالبزل وذلك خلال الفترة ما بين ايار 2015 وحتى تموز 2016.وكان عدد المرضى في عينة البحث 236 مريضا. تم أخذ قصة سريرية مفصلة للمرضى. تم تسجيل موجودات الفحص السريري من شحوب أو تعب أو نقص شهية أو نقص وزن، كما تم البحث عن وجود ضخامات العقد اللمفاوية أو ضخامة الطحال والكبد. تم تسجيل الموجودات المخبرية للمرضى. قمنا بإجراء بزل وخزعة نقي العظم لكل المرضى الذين تم ادخالهم في الدراسة، وتمت قراءة بزالة نقي العظم من قبل أخصائي أمراض الدم، كما تم قراءة خزعة نقي العظم من قبل أخصائي التشريح المرضي. النتائج: كانت الخزعة مشخصة في 120 حالة بالمقارنة مع 64 حالة مشخصة عن طريق البزل، وكانت حساسية ونوعية الخزعة 100% لتشخيص النقائل وتليف النقي وفقر الدم اللاتنسجي، وكانت نوعية البزل مرتفعة لتشخيص عسر تصنع النقي والإصابات الانتانية. بينما كانت حساسية البزل مرتفعة لتشخيص النقائل وتليف النقي. كان التشخيص الأكثر مشاهدة عند مرضى الدراسة هو النقائل الورمية. الخلاصة: إن بزل وخزعة نقي العظم إجراءان مهمان لدراسة نقي العظم. كما أن بزل وخزعة نقي العظم إجراءان متكاملان لوضع التشخيص. يفضل إجراء دراسة لنقي العظم عند المتقدمين بالعمر عند وجود إي اضراب دموي. وعند وجود فقر دم معزول أو نقص عناصر دم شامل يفضل إجراء كل من بزل وخزعة نقي العظم لأن ذلك يزيد نسبة الوصول إلى التشخيص. لتقييم الهوادة الدموية عند المرضى قيد العلاج الكيماوي يفضل إجراء خزعة نقي العظم. وعند الشك بوجود مرض انتاني مسبب للاضطراب الدموي المخبري يفضل الاكتفاء بإجراء بزل نقي العظم. يجب إجراء خزعة نقي العظم عند كل بزل فقير الخلوية.